Pengaruh Ujaran Kebencian Admin @KeretaCepatID pada sosok Patrick Kluivert (Pelatih Timnas) terhadap Tingkat Persepsi Followers di Media Sosial X - Brigita Probowati; A Yuda Triartanto; Akhmad Syafrudin Syahri (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
Social media has become a new communication space that allows for the rapid and widespread dissemination of information, including on public issues. One of the platforms that is often used is social media X (formerly Twitter), where users can express their opinions and shape public perception. This study is entitled "The Influence of Hate Speech by Admin @keretacepatid on Patrick Kluivert (National Team Coach) on the Level of Followers' Perception on Social Media X" which aims to determine how hatred influences the formation of perceptions of social media users. This study uses a quantitative approach with a survey method and data collection techniques through online questionnaires to followers of the @keretacepatid account. The results of the study indicate that there is a significant influence of hatred on followers' perceptions. Some respondents showed a dominant attitude, namely agreeing with the negative narrative built by the account against Patrick Kluivert, while others were in a negotiating position, namely understanding the context of the speech but still considering Kluivert's professional background as a national team coach. This finding is the importance of ethical and responsible digital communication management in shaping public opinion in the era of social media.